PERAN KOMUNIKASI KELUARGA DALAM MENUMBUHKAN MOTIVASI BERPRESTASI SISWA SELAMA MASA COVID-19 - Alya Dwi Salsabila; Yani Tri Wijayanti; Latifa Zahra (Linimasa : Jurnal Ilmu Komunikasi, 2022)
ABSTRACT The COVID-19 pandemic is a disease outbreak that spreads very widely throughout the world, including Indonesia on March 2020. The pandemic has an impact on all areas of life, one of which is the education sector. The government has taken a policy to study from home, as an effort to reduce the impact of the spread and sufferers of Covid-19. Parents have an important role as long as students study at home. The teaching and learning process, which was previously face-to-face, has been changed to online. This online learning and teaching process has been running for more than a year, making many students feel bored, less productive and passive in terms of motivation to reach achievement. But this doesn’t apply to students at MAN Insan Cendekia Ogan Komering Ilir, South Sumatra Province, even though in the midst of the pandemic they still have a myriad of achievements. Family communication by parents to increase their children's motivation is one of the influential factors. This study aims to determine the magnitude of the influence of family communication on student achievement motivation in the midst of the COVID-19 pandemic.